PENERAPAN MANAJEMEN RISIKO DAN PENYELESAIAN KREDIT MACET PRODUK DANA KREDIT UMUM PEDESAAN (KUPEDES) (Studi Pada PT. Bank Rakyat Indonesia (Persero) Tbk. Unit Dinoyo 1 Malang) - Permatasari, Ita Octaviani (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This research is on PT. Bank Rakyat Indonesia (Persero) Tbk. in the unit of Dinoyo 1 in Malang, whose objective is to illustrate and analyze the implementation of risk management and the resolution of non-performing loan for Kupedes. This descriptive case study illustrates the risks that may arise from the product, the application of risk management, and the measure the bank has taken to overcome bad debts, which will then be compared with the NPL values of several periods to determine the success of the risk management implementation. The results indicate that the risks for the bank in regard to their product are operational risk, credit risk, and reputation risk. The focus of this research is credit risk, which is influenced by macro and micro factors of the bank. To minimize the risk, the bank has implemented risk management. However, the measure has not been considered successful since the NPL value remains fluctuating compared to their 2017 Budget Work Plan (RKA) which is of 1,58%.Keywords : NPL, Risk Management, Credit Risk